Cardiovascular risk in aging adults with double deficits in social support: A gender-sensitive, cross-sectional analysis of the CLSA cohort - Annalijn I. Conklin; Abdollah Safari; Gerry Veenstra; Nadia A. Khan (PLoS ONE, 2025)
Background Synergistic effects of diverse social supports (informational, tangible, emotional and belonging) on cardiovascular disease risk factors (CVRF), by gender, is unknown. Aim To quantify gender differences in the singular and combined associations of four different forms of social support with cardiovascular disease risk factors (CVRF) in aging adults. Methods Cross-sectional study of 28,779 adults (45−85 years) in the Canadian Longitudinal Study on Aging Comprehensive cohort (2011−15); independent variables were self-reported measures of informational, tangible, emotional and belonging support; dependent variables were clinically measured BMI, waist circumference and blood pressure. We used stratified multivariable linear and logistic regression with principal component regression with cross-product terms to post-estimate adjusted means and 95% CIs for combined associations. Results All low-low support combinations were consistently associated with the highest adjusted mean BMI and WC levels among women. Adjusted mean BMI differences were largest among women with low informational and low tangible supports (27.95 kg/m 2 [27.93, 27.97]), compared to women with high informational and high tangible supports (27.34 kg/m 2 [27.30, 27.38]). Similarly, the greatest difference in adjusted mean WC was seen among women with low informational and low emotional supports (88.69 cm [88.62, 88.76]) compared to the high-high combination (86.88 cm [86.75, 87.01]). Women with low availability of informational support, with or without deficits in a second support type, had the highest adjusted mean SBP levels (range: 119.94 to 119.95 mmHg). Among men, mean CVRFs were not consistently worse for combinations of dual deficits in social support. Results were null for DBP. Conclusion Women with two deficits in social supports, particularly combinations with low informational support, showed worse CVRF measures than one social support deficit. Results indicated no antagonistic/synergistic effects of social support on CVRFs. Heart health care and prevention for aging women would benefit from ensuring informational support with other supports is available.